2021
DOI: 10.3390/ijerph18073343
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of SARS-CoV-2 among Healthcare Workers in a North Italy Hospital

Abstract: Background: Healthcare workers (HCWs) have been the key players in the fight against the coronavirus disease 2019 (COVID-19) pandemic. The aim of our study was to evaluate the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgG anti-bodies. Methods: We conducted a cross-sectional study among workers of two hospitals and Territorial Medical and Administrative services in Northern Italy. From 8 May to 3 June 2020, 2252 subjects were tested. Seroprevalence and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
3
9
1
1
Order By: Relevance
“…HCWs from emergency departments reportedly have a lower percentage of seropositivity (5.9%) [ 36 ]. In contrast with our study, Airoldi et al [ 37 ] found that female HCWs have higher odds of seropositivity OR 1.29, 95% CI (0.92 to 1.80), but other studies have shown, like our study, that male HCWs have a higher ORs [ 26 , 38 ]. Similar to our study, studies have confirmed the increased odds of seropositivity in physicians compared to nurses and other HCWs [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…HCWs from emergency departments reportedly have a lower percentage of seropositivity (5.9%) [ 36 ]. In contrast with our study, Airoldi et al [ 37 ] found that female HCWs have higher odds of seropositivity OR 1.29, 95% CI (0.92 to 1.80), but other studies have shown, like our study, that male HCWs have a higher ORs [ 26 , 38 ]. Similar to our study, studies have confirmed the increased odds of seropositivity in physicians compared to nurses and other HCWs [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Health workers (HW) have a substantial risk of contracting SARS-CoV-2 due to their frequent and intensive contact with infected patients [ 1 ]. In Northern Italy, which was particularly hit by the first COVID-19 wave in Europe, seroprevalence was 28.5% in HW with a high exposure to infected patients compared to 12.8% in the low exposure group [ 2 ]. In Spain, similar infection rates were found.…”
Section: Introductionmentioning
confidence: 99%
“…Other national studies were conducted among hospital healthcare workers in the same Italian provinces and the prevalence ranged from 5.13% to 8.62% ( Amendola et al , 2020 ; Paderno et al , 2020 ; Sotgiu et al , 2020 ; Calcagno et al , 2021 ), coherent with our estimates. Only in one study an extreme value of 17.11% was observed ( Airoldi et al , 2021 ). Finally, in an Italian study ( Vena et al , 2020 ) conducted in March–April 2020 ( n = 3609) in close geographical area, the authors observed that occupational exposures and living in a long-term care facility increased the probability of being seropositive with Odds Ratios of 2.60 [95%CI 1.76–3.88] and 7.56 [95%CI 5.58–10.23], respectively.…”
Section: Discussionmentioning
confidence: 98%